Shoreline and Mangrove Analysis along Semarang-Demak, Indonesia for Sustainable Environmental Management - Irsadi, A.; Anggoro, S.; Soeprobowati, T. R.; Helmi, M.; Khair, A. S. E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
This study analyses changes in shoreline and mangroves status at the gulf coast of Sayung-Demak, Indonesia. Data on shoreline changes were from high-resolution imagery in 2005, 2010 and 2017 by ArcGIS 10.3, while mangrove diversity data were observed from field studies using the transect method at three locations at the Semarang-Demak beach frontier. Based on the analysis and calculations, it was found that the coastline was decline by 0.49 km from 2005 to 2010, and incline by 3.30 km from 2010 to 2017. Abrasion occurred was 285.07 ha and accretion of 2.40 ha. The composition of mangroves on the border of Semarang-Demak consists of A. alba, A. marina, R. mucronata, R. stylosa, S. casseolaris. For this reason, it is necessary to monitor changes in shoreline and the status of mangroves on the Semarang-Demak border. In addition, it is essential to do integrated environmental management in coping with abrasion.